A mixed methods study examining perceptions by service-users of their involuntary admission in relation to levels of insight. (December 2022) - Smyth, Siobhan; McFarland, John; McGuiness, David; Summerville, Sarah; Bainbridge, Emma; Hallahan, Brian; Higgins, Agnes; Casey, Dympna; Murphy, Kathy; McDonald, Colm
Background: Poor insight is associated with negative attitudes to involuntary admission and care in qualitative studies. Aims: The current paper aims to examine and compare retrospective qualitative perceptions of service-users in relation to their involuntary admission with their levels of clinical insight, using a mixed methods approach. Methods: Forty two participants were assessed 3 months after the revocation of their involuntary admission. Each provided qualitative data relating to their perceptions of the coercive care process, which was analysed using content analysis, along with a quantitative measurement of insight, the Schedule for the Assessment of Insight-Expanded (SAI-E). Employing a mixed methods design and incorporating NVivo matrix coding queries, the datasets were merged to enable qualitative themes to be identified against the quantitative data. Results: Differences were observed between those with high and low insight in terms of their understanding of the need for treatment, their levels of arousal at the time of admission and how they perceived the compassion of health professionals. Certain negative perceptions of care appeared more universal and were common across those with high and low insight. Conclusion: Some negative perceptions of coercive practices appear linked to inherent elements of psychotic illness such as unawareness of illness. Individuals with higher levels of insight tended to perceive their involuntary admission and receiving a diagnosis as beneficial. Negative views that persist amongst service users with high insight levels can highlight areas for successful service improvement, including increased emphasis on non-pharmacotherapy based supports during the coercive care process.